Trans-scalar prisms in the study of migrations - García Castaño, F. Javier; Álvarez Veinguer, Aurora; Rubio Gómez, María (Revista de Antropología Social, 2011)
This article aims to reflect on the way social anthropology can contribute to the study of migrations and, simultaneously, to “find out” what the discipline can also learn from this field of study, and thus to transfer its knowledge to other areas. From here we will learn how important here and there are for the study of migrations, not as situations or places, but as constructed and reconstructed notions of identification processes. From that point, we will try to show some examples of our ethnographic research that lead to the analysis of the concept of situation from its relational dimension. A notion of context that shouldn’t be seen in relation to space, but in the provision of meanings for the social and cultural events within it. Therefore a trans-scalar approach of anthropology will arise in a global context and referring to any sociocultural pnenomenon. Such an approach wil lead to the enforcement of a multisited ethnography.
Keywords: Migrations; Multi-sited Ethnography; Trans-scalar Approach